2019
DOI: 10.5194/aab-62-423-2019
|View full text |Cite
|
Sign up to set email alerts
|

Time of sexual maturity and early egg quality of Japanese quails affected by in ovo injection of medicinal plants

Abstract: The aim of this study was to evaluate the time to sexual maturity and quality of initial eggs of Japanese quail affected by in ovo injection of plant extracts: ginger (GR), garlic (GC), oregano (O) and cinnamon (C). In total, 2400 eggs of Japanese quails were divided into six groups on the fifth day of incubation. Group I was the control group (NC), which was not injected. Other eggs were injected with 0.1 mL of liquid: group II – the positive control (PC) – with distilled water, group III with 1 % solution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In chicken eggs it is confirmed that larger eggs are characterized by bigger albumen proportion as well as height of dense fraction of albumen [23]. However, in the case of quail eggs these relationships are not so unequivocal [24].…”
Section: Discussionmentioning
confidence: 96%
“…In chicken eggs it is confirmed that larger eggs are characterized by bigger albumen proportion as well as height of dense fraction of albumen [23]. However, in the case of quail eggs these relationships are not so unequivocal [24].…”
Section: Discussionmentioning
confidence: 96%
“…Injection in ovo of plant extracts (garlic) into Japanese quail eggs improved the laying rate, shell strength and proportion of yolk. This injection modified both the timing of sexual maturity and the quality of the initial eggs [ 51 ]. In our case, we found a decrease in egg weight in the GSE group, which was associated with lower fatness around the ovary and a lower fat volume at 37 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…The commercial, chemically pure powdered plant extracts of ginger (GR, Zingiber officinale ), garlic (GC, Allium sativum ), oregano (O, Origanum vulgare ), and cinnamon (C, Cinnamomum verum ) were used. The content of chosen phytochemical in PEs were analyzed as it was described before ( Al-Shammari et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%